KONSEP PENDIDIKAN KARAKTER PADA ERA REVIVALISME ISLAM DI INDONESIA (STUDI PERBANDINGAN PEMIKIRAN KH HASYIM ASY’ARI DAN KH AHMAD DAHLAN) - Nurhaizan Sembiring, Ghaffariel Insani Aura, Ramlan Padang, (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2022)
At the beginning of the 20th century, Islamic society in Indonesia entered a decline phase, while the Western world experienced a progressive phase, namely the modern phase. At that time, the Muslims were confused about finding guidance in life due to the presence of the Dutch and Japanese colonials to colonize the natural resources and human resources of the Indonesian nation. KH Hasyim Asy'ari and KH Ahmad Dahlan as the nation's founding fathers were present in the midst of society in the era of Islamic revivalism to fight for the fate of a nation that was in the midst of a decline in character education. The Islamic revivalism movement is a movement for the revival of Muslims against internal as well as external self. At that time, KH Hasyim Asy'ari saw the various kinds of immorality committed by the Tebuireng village community, which were caused by a lack of Islamic character education. The same thing happened in Kauman village, Kiai Dahlan's hometown, here and there the community practiced superstition, bid'ah and churafat (TBC). In compiling this thesis, the authors used the research method of library research (library research). Primary data in the preparation of this thesis the author uses several references, namely: 1) Noble Moral Guidance for Teachers and Students Translation of Adabul 'Alim Wal Muta'allim by Sholih Ilham; and 2) K.H. Ahmad Dahlan 1868-1923 by Abdul Mu'thi et al. KH Hasyim Asy'ari and KH Ahmad Dahlan have similarities and differences in viewing Islamic character education. However, in general the two founding fathers of this nation agreed to save Muslims from Dutch and Japanese colonial rule by trying to revive the fading Islamic character in the identity of the nation's children at that time. With regard to this research, it can be concluded that there are similarities and differences in Islamic character education according to the perspective of the two figures, namely: 1) character education for the community; 2) character education in educational institutions; 3) character education for educators and students; and 4) character education for women.